Bis(calix[4]diquinone) receptors: cesium- and rubidium-selective redox-active ionophores. - Webber, P; Beer, P; Chen, G; Felix, V; Drew, MG (2003)
A new class of redox-active ionophore comprised of two calix[4]diquinone moieties connected through either alkylene or pyridylene linkages has been developed. Spectroscopic and electrochemical investigations, X-ray crystal structure analyses, and molecular modeling studies show butylene- and propylene-linked members of this family of redox-active receptors exhibit remarkable selectivity preferences and substantial electrochemical recognition effects toward cesium and rubidium cations.